From Concepts to Care: Review of Hemiparesis due to Cerebral Palsy (Functional Plant Breeding Journal, 2022)
The present study takes advantage of the authors' anguish and embarrassment about the health-disease-care process in the face of hemiparesis, considering the contextual possibilities. Thus, it uses the empiricism of an author-student and, in a complementary way, adds qualitative fundamentals of content analysis of works published in the last decade on the subject, found in the Biblioteca Virtual em Saúde (BVS) search platform, following criteria explicit methodological guidelines in the text. Its result is the production of an elucidative, synthesized, contemporary and scientific-based material on the conceptual, anatomical, physiological and care process aspects involved in Hemiparesis resulting from Cerebral Palsy. Simultaneously, it ratifies the damages of a fragmented teaching, based on stagnant or compartmentalized disciplines, which is still hegemonic in health courses in Brazil, and in which it results in lags in the understanding of the integrality and transversality of knowledge, which can be a substantial generator of “anguish” and “embarrassment” in the academic environment, and likely to reverberate negatively in the therapeutic conduct of future health professionals.
Keywords: Health Integrality; Primary Care; Hemiparesis